Perfil biográfico de Juan Byron Markholz. - MONTAGNE V, Alfonso (Revista Médica Herediana, 2013)
The life of Dr. Juan Byron fills of pride the history of medicine of our nation. Peruvian by birth, he lived in Lima during the second half of the IXI century. Survivor of the war against Chile where his knowledge saved many lives, he was the founder of the medical society “Union Fernandina” and of its journal “Crónica Médica”. Journalist, author of dramas, meteorologist, poliglot, bacteriologist and epidemiologist, researcher and teacher of great prestige in the United States of America and a martyr of medicine. None the less this has not been enough spread. Being close to the centennial of his dead (8th May 1,995), I believe it is the right time to make known the most important aspects of his life.